Sectoral patterns of technical change: Towards a taxonomy and a theory - Pavitt, Keith (Research Policy, 1984)
Previous representations of the processes of technical change found in economics are deficient because they make the production of technology and innovations exogenous and they do not reflect the considerable variety of the sources. It is vital to systematically build a body of knowledge - based on both data and theories-that includes the production of technology and reflects sectoral diversity. Using data collected by Townsend et al. regarding the characteristics of 2000 significant British innovations and innovating firms from 1945 to 1979, the sectoral patterns of technical change are considered. Similarities and differences among sectors in the sources, nature and impact of innovations - defined by the sources of knowledge inputs, the size and principal lines of activity of innovating firms, and the sectors of an innovation's production and main use - are described and explained. The two central characteristics of innovations and innovating firms that emerged are: (1) most knowledge applied by firms in innovations is not general purpose and easily transmitted and reproduced, rather it is appropriate for specific applications and for specific firms; and (2) sectors vary in the relative importance of product and process innovations, in sources of process technology, and in the size and patterns of the technological diversification of innovating firms. In order to categorize and explain these characteristics, a taxonomy and theory of sectoral patterns are proposed, based on whether a sector is primarily supplier dominated, production intensive or science based. A close relationship is found between investment in user sectors and innovative activities in upstream capital goods. In addition, an explanation of the balance in different sectors between product and process innovation is offered and expectations regarding the degree to which firms develop their own process innovations or buy them from upstream suppliers of production equipment are presented. The taxonomy offers insight into (1) the R&D and technological mechanisms of diversification or of economic activity within sectors, and (2) how technical change may have an economic impact on firms. The links at firm level between firm strategy and R&D strategy are also identified. Finally, the technological trajectories of firms, as a function of their principal activities, are identified, which makes a prediction of the future paths of technological diversification across product lines and sectors possible. (SFL)